Efforts to increase nursing students' knowledge on the management of progressive mobilization in the intensive care unit - Agustin, Wahyu Rima; Tobi, Hermiana Ernastin; Prabowo, Ari (Community Empowerment, 2024)
Progressive mobilization is a stepwise intervention provided to critically ill patients in the intensive care unit (ICU) to support the recovery of hemodynamic status through physical activities such as head-of-bed (HOB) elevation and range-of-motion (ROM) exercises. This intervention is an essential part of nursing care plans in the ICU. This community service program aims to enhance the knowledge and skills of nursing students in implementing progressive mobilization for ICU patients. The program utilized interactive lectures and question-and-answer sessions delivered through educational media such as slide presentations and the Zoom Meeting platform. Evaluation results demonstrated a significant improvement in participants' understanding. Before the training, the pre-test revealed that 60% (97 participants) had limited knowledge of progressive mobilization techniques. After the training, the post-test showed that 90% (146 participants) had a proper understanding of these techniques.